PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS V SDN 78 PEKANBARU - Nur Afni Fitri; Jesi Alexander Alim; Hendri Marhadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract: This study aims to improve student learning outcomes Math 078 class Pekanbaru SDN Academic Year 2012/2013 through the "Application of Cooperative Learning Model of type Student Teams Achievement Division (STAD)". This study was conducted in May 2013 until June 2013. Subjects were 078 fifth grade students of SDN Pekanbaru the number of students by 35 people. This research is a form of action research class consisting of 2 cycles. Cycle I consists of 3 sessions and on to the second cycle consists of 3 sessions. Key measurements include student learning outcomes after the action in each cycle (Deuteronomy Deuteronomy Daily Diary I and II). Instruments include the study of learning (syllabus, lesson plans, worksheets, Sheet achievement test), the observation sheet / observation of student activity and teacher activity. The data were analyzed descriptively. Research data shows that the learning outcomes of students has increased, which prior to the action of 35 students just as much as 20 students (57.14%) were scored daily tests above or equal to a minimum completeness criteria (KKM) as determined by the school ie 70. while as many as 15 students (42.86%) is still below the KKM. After the first cycle the action as much as 65.71% of students received grades above daily tests KKM KKM or equal to, the second cycle to as much as 85.71% of students received grades above daily tests KKM. Activities of students during the learning process (Cycle I and Cycle II) categorized Both with an average 71.81%, while for teachers also categorized Neither activity with an average of 74.22%. It can be concluded that this hypothesis "if applicable models STAD cooperative learning in the learning process of mathematics, it can improve learning outcomes math fifth grade students of SD N 78 Pekanbaru acceptable.